Maintenance Of Loading and Unloading Equipment To Support The Fair Of The Loading and Unloading Process In MV. Golden Destiny - Mega Nanda Ayu; Oktrianti Diani (IWJ : Inland Waterways Journal, 2023)
lift cargo from the ship's hold, then transferred to the dock.Damage to ship cranes is a problem that often occurs in the loading and unloading process on bulk carrier ships that have cranes on the ship. Ship cranes function as one of the most important loading and unloading tools in the loading and unloading process. In order for the loading and unloading process to run smoothly, it is possible to determine the factors that cause damage to the ship's crane, how to prevent damage to the ship's crane, and prevent damage to the ship's crane. The method used by researchers to solve the problem is descriptive, qualitative method so that researchers can describe the results of the research obtained.Collecting data through documentation, observation and interviews. Researchers conducted direct observations on board the MV.Golden Destiny, researchers conducted interviews with the 1st officer and bosun. Researchers also took pictures to support the observation of research data. The results of the study show that the factors that greatly affect the non-fluency of the loading and unloading process are damage to the ship's crane such as the entanglement of the wire crane, the broken safety roller, the way to repair the damage to the ship's crane is to replace the damaged wire crane, as well as maintenance to prevent damage to the crane. Ship which can cause the loading and unloading process not smooth on the ship.